CODE DEVELOPMENT OFF DESIGN ANALYSIS FOR AXIAL TURBINE - BADRUZ ZAMAN, M.
Turbo engines are currently widely used in the world as a power generation unit can also be applied in the fields of aerospace, aviation, marine, nuclear, etc. One type of turbo engine is a turbojet. The main components of a turbojet engine are the air intake, compressor, combustion chamber, turbine, and nozzles. One of the turbine types used in turbojet engines is axial turbine. The turbine’s function is to convert the kinetic energy contained in the fluid flow into mechanical energy that can rotate the rotor and the rotation will be transferred to the compressor. Various studies have been carried out to obtain turbine performance predictions using various methods, namely experimental methods, numerical methods (CFD), and analytical methods. However, the experimental method is considered less effective in terms of time and cost used during test when compared with the numerical method. Welch (2011) does a study to determine the performance of axial turbines. One of the methods used in this research is Computational Fluid Dynamics (CFD). Numerical solution (CFD) is a good solution for analyzing or predicting axial turbine performance. However, the CFD solution also has disadvantage, it requires high computational costs and takes a long time to get an overview of the turbine performance map being studied when compared to analytical methods. Therefore, various analytical models have been developed to predict the performance of the axial turbine. The purpose of this research is to find out how to implement a method to predict the axial turbine performance map, to find out how the level of accuracy of this method being compared to the CFD method, and how to predict the result of pressure loss coefficient. Ainley and Mathieson (1951) began to publish an analytical method that can be used to predict axial turbine performance maps. After that, the development of analytical methods to predict turbine performance maps continued to grow until in 2005, Aungier published the hub to shroud method. This method is used in this research to create a program that can predict turbine performance maps. This research begins with a literature study conducted to understand the important parameters used in determining the turbine performance map. The research continued by compiling an algorithm and applying it to the FORTRAN programming language. After the program has been completed, the program will be carried out in several case studies and analyzed how the results of the axial turbine performance map are produced. The result of this study is the form of a turbine performance map graph, predictions of losses that occur, and the flow properties produced by the turbine. The program created produces a small difference in the turbine operation area which has a low mass flow rate. However, the difference is quite large in the turbine pressure ratio in the turbine operation area that has entered the chocking area. In addition, the details of the properties of air flow that pass through the turbine at the nozzle inlet, nozzle outlet, and rotor inlet sections, the difference from each property has a small value. However, the difference starts to get bigger in the flow property at the rotor outlet. The pressure loss prediction in this study shows that the largest loss is generated due to the loss caused by the gap in the rotor at the tip of the blade. In addition, the coefficient value generated by the program in this study always has a lower value when compared to